Synergy between the Government and Pesantren in Achieving Economic Self Reliance of Islamic Boarding Schools - Robi'ul Afif Nurul 'Aini; Moch Solich (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2025)
Pesantren (Islamic boarding schools) are traditional Islamic educational institutions that have been deeply rooted in Indonesia’s history and culture, long before the introduction of the formal school system. As centers of religious learning, pesantren not only teach Islamic sciences but also nurture the character, morals, and spirituality of the students (santri) who live in dormitory environments under the direct guidance of a kiai (religious leader). Given their crucial role in shaping morally upright and religiously knowledgeable generations, the government has provided substantial support through the Pesantren Endowment Fund, as stipulated in Presidential Regulation Number 82 of 2021. This fund originates from the national Education Endowment Fund and is permanent in nature (the principal amount is not depleted), with the aim of ensuring the sustainable development of pesantren education. Through this funding, pesantren are expected to continuously improve the quality of their education, broaden access, and strengthen their contributions to national development without compromising the distinctive identity and noble values passed down through generations. This study uses a descriptive quantitative approach, employing the Product Moment Formula for data analysis. The research results show a calculated t-value (t-count) of 16.6105 and a critical t-value (t-table) of 1.67591. Since t-count > t-table, the hypothesis is accepted. The coefficient of determination is 65%, indicating a significant relationship between variable X and variable Y.